Historical Reindeer Corrals as Portraits of Human-Nature Relationships in Northern Finland - Stark, Sari; Manninen, Outi H.; Ilmolahti, Oona; Lähteenmäki, Maria (The Arctic Institute of North America, 2022)
Reindeer herding has been practised in northern boreal and subarctic regions of Fennoscandia for several centuries. The gathering and separation of reindeer for slaughter and calf marking are significant and cyclical activities of reindeer herding that are commonly carried out in reindeer corrals composed of circular-shaped fences of wood or stone construction leading into the corral. Using archaeological databases, we mapped historical reindeer corrals in northern Finland dating from the late 1800s to the 1960s for the entire reindeer herding area and characterized the legacies of their past use on present-day vegetation in Peräpohjola. In total, 94 corrals were located. Reindeer separations created a niche for novel plant communities with increasing graminoids in relation to dwarf shrubs and formation of a dense birch grove. Corrals have also preserved old rare trees left standing inside the corral to provide shelter for reindeer. The positioning of the corrals in the landscape was usually planned in a way that utilized man-made constructions and natural barriers, such as peatlands, and the typical behaviour of the reindeer in combination with both. When the wooden constructions had collapsed and decomposed, only the different vegetation indicates their past existence. L’élevage des rennes est pratiqué dans les régions boréales et subarctiques nordiques de la Fennoscandie depuis des siècles. Le rassemblement et la séparation des rennes à des fins d’abattage et de marquage des veaux sont d’importantes activités cycliques de l’élevage des rennes. Elles s’effectuent généralement dans des enclos à rennes composés de clôtures circulaires en bois ou de constructions en pierre menant aux enclos. À l’aide de bases de données archéologiques, nous avons dressé la carte historique des enclos à rennes du nord de la Finlande de la fin des années 1800 jusqu’aux années 1960 pour l’ensemble de la zone d’élevage des rennes, puis nous avons caractérisé l’héritage de leur utilisation antérieure sur la végétation actuelle de ...